Effect of salinity on growth, of juvenile dormitator latifrons (Richardson, 1844) - Acosta-Moran, Anel; Vega-Villasante, Fernando; Ruiz-Velazco, Javier M. J.; Nieves-Rodriguez, Karen; Badillo-Zapata, Daniel (Ecosistemas y Recursos Agropecuarios, 2023)
Dormitator latifrons, a native euryhaline species belonging to the family Eleotridae, is distributed from southern California to Peru. This research study is a contribution to evaluate the effect of different salinity concentrations (0, 10, 20 and 33 UPS) on growth, survival, hematology and blood chemistry. The results show statistical difference (P < 0.05) in the treatment at 10 UPS in weight per individual (91.5 ± 7.5 g), final biomass (2286.3 ± 188.3 g) and weight gain (55.5 ± 5.9 g). In the hematological parameters, statistical differences (P < 0.05) were found in the total erythrocyte count (× 106), with the highest value (4.33 ± 0.49) in the 20 UPS treatment and the lowest value (2.77 ± 0.13) in the 0 UPS treatment; survival was greater than 90.7% in all treatments. Finally, it can be concluded that the 10 UPS treatment had a greater influence on the weight (g) of Dormitator latifrons juveniles, and the GP and EA growth rates increased proportionally in the 10 UPS treatment. The results show that salinity influences the growth of the organisms despite the fact that Dormitator latifrons is a euryhaline organism. It was observed that the highest growth occurred at a salinity of 10 UPS.